2015
DOI: 10.1007/s13594-015-0244-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nanofiltration and evaporation technologies on the storage stability of milk protein concentrates

Abstract: Milk protein concentrates (MPCs) are highly nutritional and functional products manufactured from skim milk with low lactose levels. But, solubility of MPC decreases with time and temperature of storage, which often limits their application in food industries. The aim of present study is to compare the effect of nanofiltration and evaporation technologies on the rehydration stability of milk protein concentrates during storage. The MPCs produced by evaporation and nanofilteration were stored at different tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…In addition, denatured whey proteins can be bridges between casein micelles, thus increasing the number of protein‐protein interactions. The effect of ionic content on the difference in gel properties is negligible because soluble protein, calcium, phosphorus, and magnesium are present in equal amounts in NF‐MPC and EP‐MPC (Table ) (Cao et al, ). After EP‐MPC and NF‐MPC reached the gel point, the tan δ values first increased and then decreased; the maximum tan δ was observed when MPCs were gelled at different temperatures, at which point protein–protein bonds and strands in the gel were apt to relax, resulting in a greater rearrangement of both inter‐ and intramolecular forces in the gel.…”
Section: Results and Disscusionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, denatured whey proteins can be bridges between casein micelles, thus increasing the number of protein‐protein interactions. The effect of ionic content on the difference in gel properties is negligible because soluble protein, calcium, phosphorus, and magnesium are present in equal amounts in NF‐MPC and EP‐MPC (Table ) (Cao et al, ). After EP‐MPC and NF‐MPC reached the gel point, the tan δ values first increased and then decreased; the maximum tan δ was observed when MPCs were gelled at different temperatures, at which point protein–protein bonds and strands in the gel were apt to relax, resulting in a greater rearrangement of both inter‐ and intramolecular forces in the gel.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Larger micelles cause an increased number of bonds and junction zones between the casein particles. In addition, denatured whey proteins can be bridges between casein micelles, thus increasing the number of (Cao et al, 2016). After EP-MPC and NF-MPC reached the gel point, the tan δ values first increased and then decreased; the maximum tan δ was observed when MPCs were gelled at different temperatures, at which point protein-protein bonds and strands in the gel were apt to relax, resulting in a greater rearrangement of both inter-and intramolecular forces in the gel.…”
Section: Rheological Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rajagopalan and Cheryan (1991) suggested the use of microfiltration process for the complete removal of milk fat to produce MPCs and MPIs with excellent functional properties. Cao et al (2016) reported use of pasteurized skim milk (85°C/15 s) followed by UF and conventional evaporation. Li and Corredig (2014) heated the UF/DF retentates up to 80°C/ 15 min for the first time to study the effect of pH as well as heat treatment on calcium release during acidification process and buffering capacity.…”
Section: Raw Materials and Heat Treatmentmentioning
confidence: 99%